Breakdown Characteristics of a Fluoronitrile Mixture Gas According to Mixing Ratio and Oxygen Content for High-Voltage Power Equipment Application - Hwang, Ryul; Cho, Sung Joo; Song, Tae Hun; Lee, Bang Wook (IEEE access, 2024)
Fluoronitrile (C4F7N) has many advantages, such as high dielectric strength, low global warming potential (GWP), and short atmospheric lifetime compared to sulfur hexafluoride (SF6). C4F7N is mixed with carbon dioxide (CO2) to prevent liquefaction at the operating pressure of high-voltage power equipment. Therefore, it is essential to investigate the dielectric characteristics of the C4F7N/CO2 mixture gas for the development of environmentally friendly power equipment. The dielectric characteristics of C4F7N/CO2 at lower pressures have been previously reported. However, research into the breakdown characteristics of C4F7N/CO2 under high pressure environments is insufficient. Furthermore, the effect of oxygen (O2) content contributing to suppression of carbon soot formation by arc on breakdown characteristics of C4F7N/CO2 has rarely been investigated. Therefore, in this paper, the breakdown characteristics of C4F7N/CO2 according to the mixing ratio and O2 content were investigated while considering a high–pressure environment. The electrode arrangements were determined based on the field utilization factor in order to consider two types of electric field distribution. Alternating current (AC) and negative lightning impulse (-LI) breakdown tests were performed. From these experiments, under an extremely non-uniform electric field, it was confirmed that the dielectric strength of C4F7N 5%/CO2 95% at high pressure was about 75% of the strength of SF6. In a weakly non-uniform electric field, increasing the C4F7N content contributed to the improvement of dielectric strength by 31-77% relative to pure CO2 at the high pressure. Furthermore, it was investigated that the presence of O2 had no significant influence on improving the insulation performance.